Subacute cannabidiol alters genome‐wide DNA methylation in adult mouse hippocampus. (10th August 2020) - Wanner, Nicole M; Colwell, Mathia; Drown, Chelsea; Faulk, Christopher
Abstract: Use of cannabidiol (CBD), the most abundant non‐psychoactive compound found in cannabis ( Cannabis sativa ), has recently increased as a result of widespread availability of CBD‐containing products. CBD is FDA‐approved for the treatment of epilepsy and exhibits anxiolytic, antipsychotic, prosocial, and other behavioral effects in animal studies and clinical trials, however, the underlying mechanisms governing these phenotypes are still being elucidated. The epigenome, particularly DNA methylation, is responsive to environmental input and can govern persistent patterns of gene regulation affecting phenotype across the life course. In order to understand the epigenomic activity of cannabidiol exposure in the adult brain, 12‐week‐old male wild‐type a/a Agouti viable yellow (A vy ) mice were exposed to either 20 mg/kg CBD or vehicle daily by oral administration for 14 days. Hippocampal tissue was collected and reduced‐representation bisulfite sequencing (RRBS) was performed. Analyses revealed 3, 323 differentially methylated loci (DMLs) in CBD‐exposed animals with a small skew toward global hypomethylation. Genes for cell adhesion and migration, dendritic spine development, and excitatory postsynaptic potential were found to be enriched in a gene ontology term analysis of DML‐containing genes, and disease ontology enrichment revealed an overrepresentation of DMLs in gene sets associated with autism spectrum disorder, schizophrenia, and other phenotypes. These results suggest that the epigenome may be a key substrate for CBD's behavioral effects and provides a wealth of gene regulatory information for further study.